Effect of priming principle on the induction dose requirements of propofol in patients undergoing elective surgeries under general anaesthesia - Gvalani, S. K.; Bhodane, Suresh D. (International Journal of Research in Medical Sciences, 2016)
Background: A major disadvantage of rapid induction with propofol is hypotension at a dose of 2 mg/kg. Priming principle is an effective technique to reduce the total induction dose of propofol. The hemodynamic changes are attenuated and the cost is reduced. The frequency and severity of dose related effects also falls. Methods: This study of 100 patients was a prospective randomized controlled study. Patients were randomly divided into two groups of 50 each. The control group received 2mg/kg IV propofol till loss of eyelash reflex. The study or priming group received 30% of the calculated dose followed by the remaining dose after 30 seconds. The total induction dose and hemodynamic parameters were recorded. Incidence of apnoea and fasciculations as well as pain on injection were noted. Analysis of demographic data was done using chi-square test. Comparison between the groups for induction dose and hemodynamic parameters was done using the student ‘t’ test. A p-value of <0.05 was considered statistically significant. Results: The mean induction dose was significantly lower in the study or priming group. The difference in the heart rate was not significant except at 5 minutes after induction. Systolic, diastolic and mean blood pressure was significantly higher in the study group at all times. The incidence of apnoea was greater in the control group while fasciculations were more frequent in the priming group. Conclusions: Priming principle can be effectively applied to propofol to reduce the total induction dose with concomitant attenuation of hypotension. The only disadvantage noted was that fasciculations due to scoline were more pronounced.